Digestive tract trematodiases (invasions caused by intestinal flukes) - S. B. Chuyelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2020)
The paper summarizes information on the etiology, life cycles, epidemiology, pathogenesis, pathomorphology, clinical manifestations, diagnostics, etiotropic therapy and prevention of digestive tract trematodiases: echinostomiasis, echinochasmiasis, artyfechinostomiasis, isthmiophoriasis, hypoderaeiasis, nanophyetiasis, gastrodiscoidiasis, brachylaimiasis, acanthoparyphiasis, isoparorchiasis, gymnophalloidiasis, neodiplostomiasis, plagiorchiasis, clinostomiasis.